2022
DOI: 10.35508/jme.v1i2.6329
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Dan Peringatan Dini Terhadap Penyakit Menular Pada Puskesmas Dan Balai Pengobatan Di Kota Kupang

Abstract: Sistem pelaporan monitoring penyakit menular pada Dinas Kesehatan (Dinkes) Kota Kupang dilakukan tiap bulan. Proses pengumpulan dan pengelolahan data bersifat paper based dan manual oleh tiap 11 puskesmas dan 2 balai pengobatan. Keterlambatan dan keakuratan data laporan W2 menyebabkan pengambilan keputusan tanggap darurat penyakit menular tidak optimal. Melalui implementasi SIMOK-w2, petugas surveilans melaporkan data w2 ke server Dinkes kota untuk diproses dan dipublikasikan pada website dinkes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of this study are in line with the findings of [11], which concluded that there was no correlation between gender and pulmonary TB. In the service region of Pondidaha Public Health Center, TB cases did not differ significantly by age group in 2020-2021.…”
Section: Gender and The Incidence Of Pulmonary Tbsupporting
confidence: 91%
“…The results of this study are in line with the findings of [11], which concluded that there was no correlation between gender and pulmonary TB. In the service region of Pondidaha Public Health Center, TB cases did not differ significantly by age group in 2020-2021.…”
Section: Gender and The Incidence Of Pulmonary Tbsupporting
confidence: 91%